Swarm Intelligence: 7th International Conference, ANTS 2010, Brussels, Belgium,September 8-10, 2010 Proceedings - International Workshop on Ant Algorithms; Dorigo, Marco (Lecture Notes in Computer Science, 2010)
A book that constitutes the proceedings of the 7th International Conference on Swarm Intelligence, that was held in Brussels, Belgium, in September 2010.